The Role of Simulation-Based Training in Enhancing Healthcare Workforce Performance: A Systematic Review of Physicians, Nurses, and Healthcare Management Specialists' Experiences - Dr. Zamil Jamil Alyamani, AbdulRahman Abdulwakeel Alsulami, OMAR OBAID A ALOMAYRI, ADEL SADI AL -OMERI, Thamer Abdulaziz Alomayri, Arif Hameed Mohammed Albishri, ABDULLAH. AHMED. ASSUL, Suhaila Amer Binyameen; Samaher Faisal Alharbi, Rehab Abdullah Almotairi, Khlood zaid Alabass, Rawan Majid Allihyibi, AHMED MARWAYE NAMAZI, FAISAL HAMDAN ALSHEHRI, Ashraf Omar Alharbi, Bodour Badr Saqr ALMotairi (Journal of International Crisis and Risk Communication Research, 2024)
Background: Simulation-based training (SBT) has emerged as a pivotal tool in healthcare education, providing a risk-free environment for developing technical and non-technical skills. Its application spans various healthcare roles, including physicians, nurses, and healthcare management specialists, all of whom play critical roles in delivering high-quality care. Objective: This systematic review aims to evaluate the role of SBT in enhancing the performance of physicians, nurses, and healthcare management specialists. It explores its impact on clinical skills, teamwork, decision-making, and overall workforce effectiveness, while identifying challenges and opportunities for optimization. Methods: A systematic review of relevant literature was conducted, focusing on studies published in the past two decades. Databases such as PubMed, Scopus, and Web of Science were searched for evidence of SBT outcomes, with particular emphasis on interdisciplinary and regional perspectives. Results: The findings demonstrate that SBT significantly improves clinical competencies, enhances interprofessional collaboration, and fosters critical thinking and confidence among healthcare professionals. Physicians reported improved procedural accuracy and decision-making, nurses benefited from increased confidence in patient care, and healthcare management specialists demonstrated enhanced leadership and crisis management skills. However, challenges such as high costs, access disparities, and the need for standardized curricula persist. Emerging technologies like virtual reality and tele-simulation present opportunities to address these barriers and expand SBT’s reach. Conclusion: SBT is an effective and versatile training approach that enhances healthcare workforce performance and patient safety. Addressing implementation challenges and leveraging technological advancements are essential to maximize its potential. Future research should focus on long-term outcomes, cost-effectiveness, and strategies to standardize and expand simulation-based training programs globally.